Evaluation Methodology of Open-Pit Mine Overall Slope Failure Risks - Natalija Pavlovic; Branko Petrovic; Tomislav Subaranovic (Materials Proceedings)
Slope failure risks and corresponding probabilities and consequences are related to a large number of causes, thus, their quantification is a complex process. The semi-qualitative method FMEA was modified into a quantitative value method V-FMEA for specific mining requirements, which enabled the risk assessment to perform a constant check of acceptable probabilities of the overall slope failure and the implementation of detection and preventive activities as functions of the present value of consequence costs. The large open-pit mine Field E slope failure served as a good example of the proposed new risk evaluation methodology.